Analisis Bauran Pemasaran Dalam Upaya Meningkatkan Keputusan Pembelian di Kopi Nako Kota Wisata - Riky Darmawan; Puspita Romadhona (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the marketing mix at Kopi Nako Kota Wisata and its impact in an effort to increase purchasing decisions at Kopi Nako Kota Wisata. This research uses descriptive qualitative methods with primary data sources. The techniques used in collecting data in this study include observation, interviews and documentation directly to respondents of Kopi Nako Kota Wisata Cibubur and literature study. The results showed that Kopi Nako Kota Wisata has implemented a marketing mix and is able to improve purchasing decisions, namely from the aspect of the products offered that are of good quality, clean and use fresh ingredients, the price aspect offered is still affordable from the surrounding cafes, the promotion aspect is good and spreads by word of mouth, the location aspect is very strategic because the location is easily accessible from various directions, the aspect of staff people where staff serve consumers in a friendly and polite manner, the process aspect where the unique menu ordering process, various payment facilities and fast product presentation, the physical evidence aspect is seen from a crowded but still conducive atmosphere and good furniture layout and monochrome aesthetics. Keywords: Marketing Mix, Purchase Decision